Use of Community Based Participatory Research to Design Interventions for Healthy Lifestyle in an Alternative Learning Environment. (May 2021) - Cristiani, Valeria; Kumbamu, Ashok; Asiedu, Gladys B.; Johnson, Shirley K.; Gewirtz O'Brien, Janna Rae; Ziebart, Gordon; Mogen, Melissa R.; Lynch, Brian; Kumar, Seema
Introduction/Objectives: Childhood obesity develops as the result of the interplay between individual and environmental factors. Community based participatory research (CBPR) is an effective tool for improving health of communities. There is limited research on CBPR for facilitating healthy lifestyle in community schools with an alternative learning environment. The objective of the study was to explore student and staff perspectives via focus groups on barriers and facilitators for healthy eating and physical activity in a community school with alternative learning environment and to prioritize, design, and implement suggested interventions to improve healthy lifestyle. Methods: We conducted qualitative research through 8 focus groups of middle and high school students (n = 40) and 2 focus groups of school staff (n = 8). The school community and research team subsequently identified and implemented interventions for facilitating healthy lifestyle in students within the school environment. Results: Barriers identified for healthy lifestyle included lack of motivation, lack of healthy food options at school, inadequate knowledge about healthy lifestyle and insufficient opportunities for physical activity. Facilitators for healthy lifestyle were support and motivation from mentors and knowledge about healthy nutrition. Key strategies implemented were addition of healthier food options, educational materials for healthy eating, creation of a walk path, standing desks in classrooms and additional equipment in the school gymnasium. Conclusions: Formative feedback from students and staff was helpful in the implementation of strategies for facilitating healthy lifestyle among students within a community school with an alternative learning environment.